Protective Role of IRBIT on Sodium Bicarbonate Cotransporter-n1 for Migratory Cancer Cells - Soyoung Hwang; Dong Min Shin; Jeong Hee Hong (MDPI AG, 2020)
IP3 receptor-binding protein released with IP3 (IRBIT) interacts with various ion channels and transporters. An electroneutral type of sodium bicarbonate cotransporter, NBCn1, participates in cell migration, and its enhanced expression is related to cancer metastasis. The effect of IRBIT on NBCn1 and its relation to cancer cell migration remain obscure. We therefore aimed to determine the effect of IRBIT on NBCn1 and the regulation of cancer cell migration due to IRBIT-induced alterations in NBCn1 activity. Overexpression of IRBIT enhanced cancer cell migration and NBC activity. Knockdown of IRBIT or NBCn1 and treatment with an NBC-specific inhibitor, S0859, attenuated cell migration. Stimulation with oncogenic epidermal growth factor enhanced the expression of NBCn1 and migration of cancer cells by recruiting IRBIT. The recruited IRBIT stably maintained the expression of the NBCn1 transporter machinery in the plasma membrane. Combined inhibition of IRBIT and NBCn1 dramatically inhibited the migration of cancer cells. Combined modulation of IRBIT and NBCn1 offers an effective strategy for attenuating cancer metastasis.